A Study of Factors Affecting Level of Satisfaction with Marketing Mix of Shrimp farming community tourism enterprise Products, Bang Len District, Nakhon Pathom Province - Chunchomnoi, Mana; Kenikasahmanworakhun, Phatthararuethai (Journal of Public Administration Chiang Rai Rajabhat University, 2023)
The objectives of this research were 1) to study the level of satisfaction with the marketing mix of Shrimp farming community tourism enterprise products in Bang Len District, Nakhon Pathom Province, and 2) to study the factors affecting the level of satisfaction with the shrimp farming mix Market of Shrimp farming community tourism enterprise Products, Bang Len District, Nakhon Pathom Province The researcher defined a sample group to be used as a representative of the population, i.e. consumers who bought products from the community enterprise of freshwater shrimp farming in Bang Len District, Nakhon Pathom Province. Because the exact number of the population is unknown causing the study to determine the sample size for which the exact number of the population is unknown using the cochrane formula Determine the allowable tolerance ratio. At a 95% confidence level and a 5% tolerance, 145 subjects were calculated. The study was a quantitative study. There are tools used in research, namely questionnaires, with an IOC value of 0.97 and a confidence value of 0.989. It can be seen that the research tool is at a very high level of confidence. The researcher selected statistics for data analysis as follows: descriptive statistics. By distribution in the form of frequency, percentage, mean and standard deviation. Inferential Analysis Statistics by finding the relationship of a given variable to explain information The statistics used to analyze the statistics used for testing were t- distribution (T-test), F-distribution (F-test ). The results of the study showed that 1) the level of satisfaction with the marketing mix of the crawfish farmer community enterprise products in Bang Len District, Nakhon Pathom Province had a high average level of satisfaction; 2) the personal factors consisted of age, occupation and the average monthly income different As a result, the level of satisfaction with the marketing mix of Shrimp farming community tourism enterprise products in Bang Len District, Nakhon Pathom Province was significantly different at the .05 level.